The problem of the quotative term exemplified by so nach dem Motto ‘atseit/allegedly’ structure / Zur Problematik des Begriffes Quotativ am Beispiel der Konstruktion so nach dem Motto - Sinkevičienė, Jurgita (Kalbotyra, 2015)
The concept of quotatives (quotation markers) has been increasingly used in the linguistic research recently. It usually appears when evidentiality is discussed. While quoting, another person’s utterance is reported exactly, preserving both the content of reported information and the external form of the utterance. This method of reporting information strongly differs from the usual definition of evidentiality as marking the source of reported information. Thus, this research paper focuses on defining the difference between quotatives and evidential markers. The research data include 100 authentic examples of so nach dem Motto ‘atseit/allegedly’ structure. The data have been collected from the following internet forums: www.dogforum.de, www.hochzeitsforum.de, www.bfriends.brigitte.de/foren. The research shows that the quotatives are used to highlight rather the form of an utterance than its content. This allows to distinguish a major difference between them, on one hand, and the evidential markers, on the other hand, the latter focusing mainly on the content of utterances, as well as to speak of the interpretive use function as defined by Sperber & Wilson (1986). The authors define the concept of interpretive use as using an utterance with reference to another utterance, i.e. when the speaker refers in his utterance to another person’s utterance or thought which resembles it, aiming to comment on that. This is exactly what can be observed in the use of structure so nach dem Motto ‘atseit/allegedly’, which reports the general content sense and often refers to another person’s attitude, mentality, nonverbal behaviour or unspoken thoughts. Abstract in German